Analysis of the Relationship between the Positional Power Sources Used by School Administrators and the Organizational Silence Behaviors of Teachers - ÖZDEMİR, ALİ (My University, 2023)
This study was conducted to examine the relationship between the positional power sources used by school administrators and the organizational silence behaviors of teachers. In the study, relational survey model, one of the quantitative research methods, was used. The sample group of the study consisted of 519 teachers working in different branches and different school types in Istanbul. "Organizational Power Resources Scale" and "Organizational Silence Scale" developed as data collection tools were used and the data obtained were analyzed through the SPSS 21.0 package program. Reliability analysis, pearson correlation analysis and regression analysis were used in the analysis of the research data. As a result of the analysis, it was seen that the reliability coefficients of the scales used in the study were high. According to the results obtained; a negative relationship was found between the power of rewarding and legal power and organizational silence. On the other hand, a positive relationship was found between coercive power and organizational silence. As a result of the regression analysis, it was concluded that the power of rewarding, legal power and coercive power were effective on organizational silence.
Keywords: Positional power; power of rewarding; legal power; coercive power; organizational silence